Understanding the pavement texture evolution of RIOH Track using multi-scale and spatiotemporal analysis. (June 2023) - Xiao, Shenqing; Li, Mingliang; Chen, Bo; Zhou, Xingye; Xi, Chenchen; Tan, Yiqiu
Abstract: To better understand the evolution of pavement texture on different scales, the self-affine characteristics and spatiotemporal variation of pavement texture were respectively analyzed via the long-term observation data from the field RIOH track. Interestingly, the texture roughness of the same pavement exhibits some small-scale similarity and large-scale variability. This variability is also reflected in the spatial variation results (less than 20%) of on-site texture depth. Moreover, the pavement texture depth presents an upward trend with a long-term service environment (traffic polishing/seasonal variation). Particularly with the participation of traffic polishing, the typical texture evolution of the enlarged particle gap and smooth particle surface was also observed.